A quick DNA extraction protocol: without liquid nitrogen in ambient temperature - Ferdous, Jannatul; Musa, Mohamed Hanafi; Yusop, Mohd Rafii; Syed Muhammad, Sharifah Kharidah (Academic Journals, 2012)
Marker assisted selection is an effective technique for quality traits selection in breeding program which are impossible by visual observation. Marker assisted selection in early generation requires rapid DNA extraction protocol for large number of samples in a low cost approach. A rapid and inexpensive DNA extraction protocol has been described for different tissues of color rice and other plant species which contain pigment and polyphenolic compound. This method has been modified from well known cetyltrimethylammonium bromide (CTAB) method where CTAB is used for DNA extraction. This protocol is simple and fast compared to other methods and no liquid nitrogen is required. Only inexpensive chemicals and ordinary laboratory equipments are enough for DNA extraction. The quantity of total genomic DNA from different tissues was almost similar which was extracted from 10 mg samples. The extracted DNA is stable and applicable to marker assisted selection, DNA fingerprinting, quantitative traits loci analysis, screening of transformants and enzymatic digestion.